Da feng da lang zhong qian jin (you hua) - Tang, Xiaohe, 1941- (Beijing : Ren min mei shu chu ban she, 1970)
Poster of Mao Zedong with a group of Red Guards on a boat or bathing platform with an expanse of water in the background filled with youths swimming and red banners.
"86-591."
Also available online
Keywords: Posters, Chinese -- 20th century; China -- History -- Cultural Revolution, 1966-1976 -- Posters